How do we help the environment from the supply chain? Study of production processes in order to integrate the supply chain with environmental efficiency (AACINI - International Journal of Industrial Engineering, 2024)
The importance of sustainability in logistics processes plus the coordination of the supply chain raise the maturity of integration through flows of materials and information together. The difference lies in the set of practices between suppliers, companies and clients in order to integrate SC with a high degree of maturity and evaluate environmentally friendly actions.The research is based on adding sustainability to each process while raising the level of integration of SC; applying it to a case study with a descriptive design where SC of a company dedicated to the construction and metallurgical of Olavarría is diagnosed. The revealed processes are relationships with suppliers, purchases, storage and modular construction process.The objective is to determine the logistics practices that provide integration to the supply chain in a sustainable way to dry modular construction.During the development, it was possible to evaluate the process from the order, considering the specific needs of each client, until the delivery to the same. Going through each stage, sustainable actions were identified that enhance the integration of the entire chain.The results indicate that integrated logistics practices can be carried out in a sustainable way, from purchases with a strategic relationship with suppliers, to a differentiated design for multiple delivery, making the delivery of up to four products with the same transport more efficient.
Keywords: sustainbility; supply chain; integration; maturity; enviroment; SC